Effect of Pressure and Flow Rates on Polymorphous Silicon‐Germanium (pm‐SixGe1−x:H) Thin Films for Infrared Detection Applications. Issue 12 (28th February 2018) - Jiménez, Ricardo; Moreno, Mario; Torres, Alfonso; Rosales, Pedro; Gomez, Víctor; Carlos, Netzahualcoyotl; Roca i Cabarrocas, Pere
Abstract : In this paper, the characterization and optimization of polymorphous silicon‐germanium (pm‐Six Ge1−x :H) thin films prepared by plasma‐enhanced chemical vapor deposition (PECVD) are reported in order to use them as thermo‐sensing films on infrared detectors. Two series of pm‐Six Ge1−x :H thin films are fabricated and characterized. In the first series, the pressure is varied in a wide range (600–2000 mTorr) using the same SiH4 and GeH4 flow rates, while in the second series the flow rate of GeH4 is varied in the range of R  = 10–90%. Fourier transform infrared spectroscopy (FTIR) confirms the large incorporation of germanium (Ge) in the solid phase. The aim is to optimize the films in terms of the temperature coefficient of resistance TCR (% K −1 ), room temperature conductivity, and noise. A significant variation in the TCR values from 3.1 to 9.9% K −1 and in the room temperature conductivity by about six orders of magnitude is observed. Finally, noise spectral density characterization is performed to evaluate the application of the pm‐Six Ge1−x :H films as thermo‐sensing elements in high performance infrared detectors (microbolometers). Abstract : Polymorphous silicon‐germanium (pm‐Six Ge1−x :H) thin films are studied in this work. The effect of the deposition pressure and the content of the precursor gases on the electrical and structural properties of the films are investigated. Surface roughness, noise, conductivity, and temperature coefficient of resistance (TCR) are analyzed with the objective to use these films as thermo‐sensing elements in infrared detectors.